Technology Pooling Licensing Agreements: Promoting Patent Access Through Collaborative IP Mechanisms - Armillotta, Monica (Munich Intellectual Property Law Center - MIPLC, 2010)
In patent communities several patentees cooperate contractually to licence the respective patented technologies to third parties. In consideration of the rising relevance of this business practice, this book discusses crucial courses and strategic considerations, which are the basis for the establishment of patent communities, both in legal and empirical regard, in order to identify the optimal conditions for successful conversion in a competitive surrounding. Thus the best conditions for the promotion of innovation are to be created.